A Prospective Cohort Study of the Clinical Predictors of Bacteremia in Under-Five Children With Acute Undifferentiated Fever Attending a Secondary Health Facility in Northwestern Nigeria - Ogunkunle, Taofik Oluwaseun; Adedoyin, Timothy Olanrewaju; Ernest, Samuel Kolade; Hassan-Hanga, Fatimah; Imam, Abdulazeez; Olaosebikan, Rasaq; Obaro, Stephen K. (Frontiers in Pediatrics, 2022)
Background Children with acute febrile illness with no localizing signs often receive antibiotics empirically in most resource-poor settings. However, little is known about the burden of bacteremia in this category of patients, and an appraisal is thus warranted. This will guide clinical practice and promote rational antibiotics use. Methods We prospectively followed up 140 under-five children who presented with acute undifferentiated fever at the emergency/outpatient pediatric unit of a secondary healthcare facility. Baseline clinical and laboratory information was obtained and documented in a structured questionnaire. We compared baseline characteristics between participants with bacteremia and those without bacteremia. We further fitted a multivariable logistic regression model to identify factors predictive of bacteremia among the cohort. Result The prevalence of bacteremia was 17.1%, and Salmonella Typhi was the most frequently (40.9%) isolated pathogen. The majority (78.6%) of the study participants were managed as outpatients. The participants who required admission were four times more likely to have bacteremia when compared to those managed as outpatients (AOR 4.08, 95% CI 1.19 to 14.00). There is a four times likelihood of bacteremia (AOR 4.75, 95% CI 1.48 to 15.29) with a fever duration of beyond 7 days. Similarly, participants who were admitted with lethargy were six times more likely to have bacteremia (AOR 6.20, 95% CI 1.15 to 33.44). Other significant predictors were tachypnea and lymphopenia. Conclusion Among under-five children with acute undifferentiated fever, longer duration of fever, lethargy, inpatient care, tachypnea, and lymphopenia were the significant predictors of bacteremia.